QASHQADARYO VILOYATI HUDUDI ATMOSFERA HAVOSINING O‘ZGARISHI VA ULARNING OLDINI OLISH CHORA-TADBIRLARI - Nazarov, M.G. (SCIENCE and SOCIETY, 2025)
The article examines the impact of industrial enterprises in the Kashkadarya basin, including oil and gas industry enterprises, on the environment, which is one of the pressing issues today. The role of natural and anthropogenic factors in the formation of these problems and measures for their elimination are described.
Keywords: anthropogenic landscape; environment; ecological risk; geoecological situation; atmospheric air; landscape